Ocrelizumab-Related Organizing Pneumonia: A Rare Pulmonary Complication in Multiple Sclerosis - Neria Bitton; Swetha Rayaroth; Anuraj Mambazhathu Sudhakaran; Eli Zolotov (Annals of Internal Medicine: Clinical Cases)
We report a case of organizing pneumonia induced by ocrelizumab in a 65-year-old man with multiple sclerosis. The patient presented with persistent fever and progressive respiratory symptoms despite broad-spectrum antibiotic treatment. Chest imaging revealed diffuse ground-glass opacities, and a transbronchial biopsy confirmed organizing pneumonia. Corticosteroid therapy led to marked clinical improvement, and ocrelizumab was discontinued. This case highlights the importance of recognizing drug-induced organizing pneumonia in patients receiving immunomodulatory therapy, particularly when standard antibiotic treatments fail. Early identification and corticosteroid intervention are critical to avoid further complications.